Pengelolaan Supervisi Akademik oleh Kepala Sekolah di SD Negeri 6 Putatsari Grobogan - Sugiyanti, Sugiyanti; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2016)
This study aims to describe the planning, execution, and follow-up of the academic supervision by the principal at SDN 6 Putatsari Grobogan. This research is qualitative. Data collection techniques with interviews, observation, and documentation. Data analysis techniques to the analysis of the groove. The process of collecting data through data reduction, data presentation, and conclusion. The validity of the data using triangulation, triangulation method, and triangulation of researchers. The results of the research, academic supervision 1. Planning in SD Negeri 6 Putatsari produce, a. Preparation of supervision schedule, b. Preparation of Instrument, c. Compile a list of teachers who would be supervised. 2. Implementation of Academic Supervision in SD Negeri 6 Putatsari, supervisor came to the class with the instruments that have been prepared to make observations of learning while noting the incident in accordance with the instrument. 3. Follow-Up Supervision Academic SD Negeri 6 Putatsari, principal with the teachers held discussions break time in the principal?s office, teachers are given the opportunity to express their opinions about the learning process has been implemented. The headmaster shows the results of further observations provide opportunities for teachers to observe and analyze it.